Driving Rural Economic Growth: Enhancing BUMDesa Employee Performance through Organizational Culture, Work Environment, and Motivation - Arisudana, Bagus Made; Suwena, Kadek Rai; Telagawathi, Ni Luh Wayan Sayang (Yayasan Riset dan Pengembangan Intelektual, 2025)
This study aims to analyze the influence of organizational culture, work environment, job characteristics, and work motivation on the performance of Village-Owned Enterprises (BUMDesa) employees in Tejakula District. The research is driven by the strategic role of BUMDesa in fostering rural economic growth and improving community welfare through effective management of local economic resources. However, challenges remain, including high levels of uncollected receivables, low employee loyalty, and underutilization of initial capital. A quantitative research approach was employed, involving all BUMDesa employees in Tejakula District as the study population. Data were collected through questionnaires, interviews, and document analysis, and analyzed using multiple linear regression techniques. The findings reveal that organizational culture, work environment, job characteristics, and work motivation significantly influence employee performance both simultaneously and partially. These results underscore the importance of fostering a strong organizational culture, cultivating a supportive work environment, designing jobs that align with employee competencies, and enhancing motivation to drive better performance. The practical implication of this research is the need for improved human resource strategies in BUMDesa to boost operational effectiveness and support sustainable rural economic development. The study serves as a valuable reference for BUMDesa leaders and village governments in designing strategic policies to enhance employee performance and institutional sustainability.